Microwave and wireless synthesizers : theory and design - Rohde, Ulrich L.; Rubiola, Enrico, 1957-; Whitaker, Jerry C. (John Wiley & Sons, Inc., 2021)
"This new edition provides a comprehensive review of the original text with the addition of updated text and illustrations. The book is divided into six chapters beginning with Chapter 1 on loop fundamentals, which provides detailed insight into settling time and other characteristics of the loop. Chapter 2 outlines noise and spurious responses of the loops. The linear approach of oscillator phase noise is very detailed and walks the reader through all the important steps and contributions, both inside and outside the loop. In Chapter 3 the authors look at special loops. Here, the DDS technique--explained in detail--should prove most interesting to the reader. Chapter 4 provides a detailed overview of loop components. Chapter 5 provides in-depth details about multiloop synthesizers and Chapter 6 is dedicated to practical synthesizer examples, which combine the techniques outlined in previous chapters"-- Provided by publisher.
Keywords: Frequency synthesizers -- Design and construction.; Phase-locked loops.; Digital electronics.; Microwave circuits -- Design and construction.; Radio frequency.; elektronické knihy; electronic books